Eksplorasi Spesies Rumput Laut dan Pemanfaatan Komoditas Budidaya di Perairan Mamolo - Zikriyani, Hikmah; Efriani Hutasoit, Murni (Jurnal Biogenerasi, 2025)
Kampung Mamolo, located in South Nunukan District, North Kalimantan, is one of the key centers for seaweed cultivation in the Indonesia–Malaysia border region. This study aims to explore the seaweed species cultivated by the local community and to examine their morphological characteristics and economic value. A qualitative descriptive method was used, involving field observations, interviews with seaweed farmers, and literature review. The findings identified nine seaweed species from three major divisions: Chlorophyta, Phaeophyta, and Rhodophyta. Among these, three species—Eucheuma cottonii, Eucheuma spinosum, and Kappaphycus alvarezii—are actively cultivated due to their high economic value as sources of carrageenan widely used in food, pharmaceutical, and cosmetic industries. Cultivation is carried out traditionally using the floating-line system, which has proven effective in supporting sustainable production. This research contributes to the documentation of local marine biodiversity and its potential to enhance coastal community livelihoods.